The Influence of Brand Ambassador Credibility, Brand Image, and Brand Awareness on Purchase Decisions for Cosmetic Products - Ardiyani, Novika; Pasharibu, Yusepaldo (Universitas Hamzanwadi, 2023)
This study examines the influences of brand ambassadors, brand image, and brand awareness on product purchasing decisions in Salatiga City, especially toward the purchase decision of Maybelline cosmetics products. The type of research used in this research is descriptive statistical research using quantitative methods. The respondent in this study is 100 women who live in Salatiga City. This research data collection used a questionnaire that is distributed to respondents through Google Forms. The test results indicate that the level of brand ambassadors and brand image has a positive influence on purchasing decisions, particularly for Maybelline cosmetics products. Meanwhile, there is no influence on product purchase decisions based on brand awareness.